SWOT Analysis for Enhancing the Competitiveness of STIE Ganesha South Tangerang as a Higher Education Institution - Putri Noor Ramayanti; Zulkifli Zainuddin; Siti Mulasih; Neila Aisha (Journal Of Applied Multidisiplinary Studies, 2025)
This study addresses a critical gap in strategic management literature by focusing on private higher education competitiveness in Indonesia's evolving academic landscape. The research aims to analyze STIE Ganesha South Tangerang's strategic positioning and identify key factors influencing its competitive development. Utilizing a mixed-methods approach, the study incorporated in-depth interviews, documentation analysis, and questionnaires with 29 participants, following Miles & Huberman's analytical framework through IFAS, EFAS, and SWOT matrices. Empirical findings demonstrate the institution's strong competitive advantages in faculty expertise, accreditation status, and industry-aligned curricula, while revealing significant challenges in marketing effectiveness and infrastructure development. External analysis identified digital transformation and governmental policies as pivotal opportunities, alongside intensifying competition and regulatory changes as major threats. The study's implications suggest implementing aggressive growth strategies emphasizing human capital development, digital integration, and strategic industry partnerships to enhance institutional positioning. These findings provide a actionable framework for private higher education institutions seeking to navigate competitive challenges while maintaining educational quality and market relevance